Esophageal Trachea, a Unique Foregut Malformation Requiring Multistage Surgical Reconstruction: Case Report - Tambucci, Roberto; Wautelet, Océane; Haenecour, Astrid; François, Geneviève; Goubau, Christophe; Scheers, Isabelle; Halut, Marin; Menten, Renaud; Schmitz, Sandra; de Toeuf, Caroline; Pirotte, Thierry; D'hondt, Beelke; et al. (Frontiers in Pediatrics, 2020)
Abnormal connections between the esophagus and low respiratory tract can result from embryological defects in foregut development. Beyond well-known malformations, including tracheo-esophageal fistula and laryngo-tracheo-esophageal cleft, rarer anomalies have also been reported, including communicating bronchopulmonary foregut malformations and tracheal atresia. Herein, we describe a case of what we have called “esophageal trachea”, which, to our knowledge, has yet to be reported. A full-term neonate was born in our institution presenting with a foregut malformation involving both the middle esophagus and the distal trachea, which were found to be longitudinally merged into a common segment, 3 cm in length, located just above the carina and consisted of esophageal tissue without cartilaginous rings. At birth, the esophagus and trachea were surgically separated via right thoracotomy, the common segment kept on the tracheal side only, creating a residual long-gap esophageal atresia. The resulting severe tracheomalacia was treated via simultaneous posterior splinting of such diseased segment using an autologous pericardium patch, as well as by anterior aortopexy. Terminal esophagostomy and gastrostomy were created at that stage due to the long distance between esophageal segments. Between ages 18 and 24 months, the patient underwent native esophageal reconstruction using a multistage traction-and-growth surgical strategy that combined Kimura extra-thoracic esophageal elongations at the upper esophagus and Foker external traction at the distal esophagus. Ten months after esophageal reconstruction, prolonged, refractory and severe tracheomalacia was further treated via anterior external stenting using a semitubular ringed Gore-Tex® prosthesis, through simultaneous median sternotomy and tracheoscopy. Currently, two years after the last surgery, respiratory stabilization and full oral feeding were stably achieved. Multidisciplinary management was crucial for assuring lifesaving procedures, correctly assessing anatomy, and planning for multiple sequential surgical approaches that aimed to restore long-term respiratory and digestive functions.